Sosialisasi Penghapusan Kekerasan dalam Rumah Tangga - Yeheskel Wessy; F Rumtutuly; Lestari Lestari; Ferdinanda S Noya; Asmirani Alam; Edy Sony; Harmoko Harmoko (Jurnal Kabar Masyarakat, 2024)
The Law on the Elimination of Domestic Violence Number 23 of 2004 has generated mixed responses among the public. A number of people are unhappy with the regulation, seeing it as an attempt to bring personal problems into the public domain. Although it cannot be denied, the issue of domestic violence is still considered a topic to be avoided in some segments of our society. This is considered a family issue that should not be discussed openly, despite the fact that various types of domestic violence continue to occur, including physical violence, sexual violence, psychological violence and economic violence. Forms of violence in the domestic sphere occur between family members, including violence from husbands against wives, wives against husbands, husbands against children, wives against children, and children against parents. Therefore, it is deemed necessary by the Klis Village Government, Moa Island District, Southwest Maluku Regency to serve as a collaborative initiative in implementing the work program between the 2023 Southwest Maluku PSDKU Unpatti KKN Students and the Klis Village Government. The aim is to hold outreach activities regarding the Elimination of Domestic Violence.